Identification of deleterious variants associated with male infertility genes in a cohort of idiopathic hypospermatogenesis patients - Nisha Sharma; Ashutosh Halder; Seema Kaushal; Manoj Kumar; Manish Jain (Frontiers in Reproductive Health)
IntroductionHypospermatogenesis is a common histopathological subtype of non-obstructive azoospermia and is characterized by a decrease in the total number of germ cells within the seminiferous tubule as a result of spermatogenic failure. Determination of genetic factors before intracytoplasmic sperm injection can prevent the inheritance of these factors, as hypospermatogenesis patients gives high successful sperm retrieval rate. This study aimed to identify the structural variants associated with idiopathic hypospermatogenesis (iHS) by analyzing patient cohorts diagnosed with azoospermia using whole exome sequencing.MethodsIt is a hospital-based observational study in which patients reporting with azoospermia due to spermatogenic failure were recruited prospectively. Comprehensive clinical history, blood samples, semen analysis parameters, and reproductive endocrine evaluation reports of 51 hypospermatogenesis patients were collected. The known genetic causes were investigated using XY fluorescent in situ hybridization and Yq microdeletion for exclusion. Whole exome sequencing was performed, and the data of 42 iHS patients was analyzed to identify single nucleotide variants associated with diagnostically important male infertility genes.ResultsGenomic analysis of SNVs identified rare deleterious candidate variants in CFTR (c.1265C>T; p.Ser422Phe), CYP21A2 (c.955C>T; p.Gln319Glu), SRD5A2 (c.737G>A; p.Arg245Gln), LHCGR (c.378A>C; p.Lys126Asn) and AR (c.2179C>A; p.Arg727Ser) genes associated with 7/42 idiopathic hypospermatogenesis patients. In silico analysis of variants shows deleterious and probably damaging effects on canonical transcripts of the genes.DiscussionThis exploratory genomic analysis conducted on idiopathic hypospermatogenesis patients shows prevalence of rare deleterious candidate variants in genes associated with human male infertility. The candidate variants in idiopathic hypospermatogenesis patients are heterozygous and genotypically associated with syndromic male infertility. The symptomatic heterozygosity leading to mild spermatogenic failure resulting in hypospermatogenesis points towards a multifactorial etiology of the disease. This study justifies the importance of genetic screening of idiopathic hypospermatogenesis patients for the presence of structural variants in known human male infertility genes.